Pharmacological profile of the neuropeptide S receptor: Dynamic mass redistribution studies. Issue 6 (3rd December 2018) - Ruzza, Chiara; Ferrari, Federica; Guerrini, Remo; Marzola, Erika; Preti, Delia; Reinscheid, Rainer K.; Calo, Girolamo
Abstract: Neuropeptide S (NPS) is the endogenous ligand of the neuropeptide S receptor (NPSR). NPS modulates several biological functions including anxiety, wakefulness, pain, and drug abuse. The aim of this study was the investigation of the pharmacological profile of NPSR using the dynamic mass redistribution (DMR) assay. DMR is a label‐free assay that offers a holistic view of cellular responses after receptor activation. HEK293 cells stably transfected with the murine NPSR (HEK293mNPSR ) have been used. To investigate the nature of the NPS‐evoked DMR signaling, FR900359 (Gq inhibitor), pertussis toxin (Gi inhibitor), and rolipram (phosphodiesterase inhibitor) were used. To determine the pharmacology of NPSR, several selective ligands (agonists, partial agonists, antagonists) have been tested. NPS, through selective NPSR activation, evoked a robust DMR signal with potency in the nanomolar range. This signal was predominantly, but not completely, blocked by FR900359, suggesting the involvement of the Gq‐dependent signaling cascade. NPSR ligands (agonists and antagonists) displayed potency values in DMR experiments similar, but not identical, to those reported in the literature. Furthermore, partial agonists produced a higher efficacy in DMR than in calcium experiments. DMR can be successfully used to study the pharmacology and signaling properties of novel NPSR ligands. This innovative approach will likely increase the translational value of in vitro pharmacological studies.